Envisioning possible futures for fish production in Indonesia - WorldFish (WorldFish, 2015)
This report summarizes the results of a systematic effort to explore possible futures for aquaculture and fisheries in Indonesia. The work described is part of a larger effort that seeks to develop a shared vision for the sectors that 1) aligns public and private investments to foster growth and economic sustainability; 2) reduces environmental impacts and improves efficiency; 3) increases access by small and medium enterprises to the financial and technical assistance necessary to transition to more sustainable practices. This document summarizes key drivers of change for the aquaculture and fisheries sectors and presents a resulting set of integrated scenarios.